2024
DOI: 10.1111/jcmm.18109
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA as a potential diagnostic and prognostic biomarker in melanoma: A systematic review and meta‐analysis

Mahdi Masrour,
Shaghayegh Khanmohammadi,
Parisa Fallahtafti
et al.

Abstract: Recently, long noncoding RNAs (lncRNAs) have been applied as biomarkers for melanoma patients. In this systematic review and meta‐analysis, we investigated the diagnostic and prognostic value of lncRNAs. We used the keywords ‘lncRNA’ and ‘melanoma’ to search databases for studies published before June 14th, 2023. The specificity, sensitivity and AUC were utilized to assess diagnostic accuracy and the prognostic value was assessed using overall survival, progression‐free survival and disease‐free survival hazar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Certain ncRNAs can serve as biomarkers for cancer as their expression correlates with specific cancer types or disease progression [ 151 ]. Evidence has demonstrated that ncRNAs play crucial roles for the early diagnosis, prognosis, and treatment of melanoma [ 152 , 153 ]. A recent meta-analysis found a combined sensitivity of long ncRNAs in diagnosing melanoma to be 72.4%, with a pooled specificity of 81.2% and an overall area under the curve (AUC) of 0.837.…”
Section: Risk Assessment Innovations and Personalized Medicine In Ski...mentioning
confidence: 99%
See 1 more Smart Citation
“…Certain ncRNAs can serve as biomarkers for cancer as their expression correlates with specific cancer types or disease progression [ 151 ]. Evidence has demonstrated that ncRNAs play crucial roles for the early diagnosis, prognosis, and treatment of melanoma [ 152 , 153 ]. A recent meta-analysis found a combined sensitivity of long ncRNAs in diagnosing melanoma to be 72.4%, with a pooled specificity of 81.2% and an overall area under the curve (AUC) of 0.837.…”
Section: Risk Assessment Innovations and Personalized Medicine In Ski...mentioning
confidence: 99%
“…A recent meta-analysis found a combined sensitivity of long ncRNAs in diagnosing melanoma to be 72.4%, with a pooled specificity of 81.2% and an overall area under the curve (AUC) of 0.837. For prognostic approaches, the HR for overall survival, progression-free survival, and disease-free survival were 2.723 (95% CI: 2.259–3.283), 2.913 (95% CI: 2.050–4.138), and 2.760 (95% CI: 2.009–3.792), respectively [ 153 ]. These findings indicate that ncRNAs could serve as innovative diagnostic and prognostic biomarkers, potentially enhancing patient management in the future.…”
Section: Risk Assessment Innovations and Personalized Medicine In Ski...mentioning
confidence: 99%